California Organization of Police and Sheriffs letter - William J. Hemby:::::: (1976)
These documents from the California Organization of Police and Sheriffs (COPS) concern its 1976 endorsement process. One letter follows up with candidates who had not returned a questionnaire about law enforcement issues, urging prompt response if they seek endorsement. The attached questionnaire asks candidates to state their positions on mandatory sentencing, binding arbitration for police and firefighters, a uniform statewide retirement system, redefining peace officer status, strengthening the Meyers-Milias-Brown Act, and handgun control. A separate invitation letter asks candidates to attend a September 25, 1976 general membership endorsement meeting in San Francisco to present their views to law enforcement members.